A scoping review of adult survivors' experiences of shame following sexual abuse in childhood. (3rd June 2019) - MacGinley, Maureen; Breckenridge, Jan; Mowll, Jane
Abstract: Shame following childhood sexual abuse (CSA) can be intensely painful and destructive to one's sense of self and place in the world. Organised around an internalised core belief of worthlessness, extreme shame presents as a major therapeutic challenge in therapy with many CSA survivors. A range of clinical and empirical literature, alongside recounts of survivors lived experience, shows that shame is an effect of CSA for many survivors. Yet research has rarely focused specifically on survivors' qualitative or lived experiences of shame. This article reports the results of a scoping review of the empirical research investigating adult survivors' experiences of shame following sexual abuse in their childhood. Conducted in March 2018, the search strategy involved on‐line searches of English language, peer review and select grey literature repositories for articles published up to the end of 2017. Of the 28 peer reviewed studies included in the review, only three studies specifically investigate adult survivors lived experiences of shame. The synthesised findings from the studies identify five themes demonstrating the pervasive and detrimental influence of shame following CSA: (1) Psychological effects and trauma symptoms; (2) Relationships and social connections and disconnections; (3) Disclosure; (4) Self concept; and, (5) The process of recovery. These findings resonate with conceptual literature and broader research on the influence of shame following violence and highlight areas for future research and clinical practice. This scoping review identifies three key gaps: a need for further research across specific populations and groups; research evaluating therapeutic interventions responding to shame; and research that specifically investigates adult survivors' lived experiences of shame following CSA.